Implementation of IoT Based Management Information System in MSMEs: Literature Review Analysis - Romadhoni, Luthfiah Aisyah; Pingkaniswari, Pasha; AS, Syafrul Hidayat; Ariztian, Rian; Zahrah, Aliyah; Tannady, Hendy (Yayasan Gema Bina Nusantara, 2025)
This study aims to analyze the implementation of the Internet of Things (IoT) in management information systems in Micro, Small, and Medium Enterprises through a literature review approach. The research method used is a systematic search by reviewing relevant journals published between 2020 and 2024, then five articles were selected to be reviewed. The articles used discuss various aspects of IoT implementation in MSMEs in various ways. The results of the study show that the implementation of IoT provides significant benefits for MSMEs, such as operational cost savings, optimization of resource use, and increased digital connectivity that helps MSMEs reach a wider and more competitive market. However, there are several major obstacles in the implementation of IoT, including high initial costs, limited technological infrastructure, low digital literacy, and issues of risk, security and data confidentiality that need to be addressed properly. This study recommends the need for support from the government, technology providers, and training institutions in the form of subsidies, capacity building programs, and digital infrastructure development. The implications of this study provide important insights for policy makers, academics, and business actors to design sustainable and relevant digital transformation strategies for MSMEs in the global era.